Comparison between remifentanil and dexmedetomidine for sedation during modified awake fiberoptic intubation - LIU, HUI-HUI (Exp Ther Med, 2015)
Cricothyroid membrane injections and the application of a coarse fiberoptic bronchoscope (FOB) below the vocal cords for topical anesthesia have a number of limitations for certain patients. Thus, the aim of the present observational study was to assess the effect of a novel modified topical anesthesia method using the effective sedation drugs, remifentanil (Rem) or dexmedetomidine (Dex), during awake fiberoptic orotracheal intubation (AFOI). In total, 90 adult patients, who had been classified as American Society of Anesthesiologists I–II, were included in the study. The patients had anticipated difficult airways and were to undergo orotracheal intubation for elective surgery. The patients were enrolled in the double-blinded randomized pilot study and received Rem or Dex for sedation during the modified AFOI procedure. The two groups received 2% lidocaine for topical anesthesia via an epidural catheter, which was threaded through the suction channel of the FOB. The main clinical outcomes were evaluated by graded scores representing the conditions for intubation and post-intubation. Additional parameters analyzed included airway obstruction, hemodynamic changes, time required for intubation, amnesia level and subjective satisfaction. All 90 patients were successfully intubated using the modified AFOI technique. The comfort scores and airway events during intubation did not significantly differ between the two groups. However, the Rem group experienced less coughing, and less time was required for tracheal intubation when compared with the Dex group. No statistically significant differences were observed in the changes to the mean arterial pressure and heart rate at any time point between the two groups. Therefore, the current study demonstrated that the modified AFOI method is feasible and effective for difficult airway management, and that Dex and Rem exhibit similar efficacy as adjuvant therapies.